2021
DOI: 10.1038/s41587-021-01037-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-activated antiviral innate immunity in the upper airways controls early SARS-CoV-2 infection in children

Abstract: Children have reduced severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rates and a substantially lower risk for developing severe coronavirus disease 2019 compared with adults. However, the molecular mechanisms underlying protection in younger age groups remain unknown. Here we characterize the single-cell transcriptional landscape in the upper airways of SARS-CoV-2-negative (n = 18) and age-matched SARS-CoV-2-positive (n = 24) children and corresponding samples from adults (n = 44), cove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
307
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(383 citation statements)
references
References 47 publications
22
307
3
3
Order By: Relevance
“…In our cohort, we were unable to observe a clear protective immune signature in the peripheral blood of PCR-positive asymptomatic individuals throughout all cellular and humoral immune analyses. Although the sample size was relatively small in our asymptomatic category, the most likely explanation for this result is a more prominent role of a tissue-resident rather than a systemic immune response, where anti-viral immunity mainly occurs locally through pre-activated innate immune stimulation in epithelial cells of the upper airways, as recently shown in a pediatric cohort 51 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our cohort, we were unable to observe a clear protective immune signature in the peripheral blood of PCR-positive asymptomatic individuals throughout all cellular and humoral immune analyses. Although the sample size was relatively small in our asymptomatic category, the most likely explanation for this result is a more prominent role of a tissue-resident rather than a systemic immune response, where anti-viral immunity mainly occurs locally through pre-activated innate immune stimulation in epithelial cells of the upper airways, as recently shown in a pediatric cohort 51 .…”
Section: Discussionmentioning
confidence: 76%
“…Although the sample size was relatively small in our asymptomatic category, the most likely explanation for this result is a more prominent role of a tissue-resident rather than a systemic immune response, where anti-viral immunity mainly occurs locally through pre-activated innate immune stimulation in epithelial cells of the upper airways, as recently shown in a pediatric cohort 51…”
Section: Discussionmentioning
confidence: 76%
“…Additional strands of evidence suggest a potential link between airway IFN-I/III competence and clinical outcome in COVID-19. Age remains the strongest risk factor for poor outcome in COVID-19, and the efficiency of IFN-I/III induction is known to decline with advancing age 59 , and appears to be greater in the nasal airways of children than adults infected with SARS-CoV-2 60 . Other relevant environmental influences, such as exposure to cigarette smoke or other viral infections, are also reported to perturb IFN-I/III responses of airway cells in ways that may be relevant to COVID-19 pathogenesis 43, 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our data in this nasal epithelial culture system is that it did not account for professional immune cells present in the nasal mucosa, for example plasmacytoid dendritic cells 62 , which are capable of more rapidly mounting an IFN-I/III response to SARS-CoV-2 63 , potentially tipping the scales in favour of the host 64 . We studied cells derived from adult donors, however it is possible that nasal cells from paediatric donors, who are naturally less susceptible to severe COVID-19, may behave differently in terms of their reduced permissiveness to SARS-CoV-2 and/or the greater efficiency of their innate IFN response 60, 65 . Furthermore, SARS-CoV-2 variants with mutations in the spike gene have emerged worldwide whilst we were undertaking the experiments described here; these variants may impact viral replication and/or host immunity, and should be included in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has repeatedly been reported that younger individuals have a significantly lower risk for developing coronavirus disease 2019 . Indeed a recently published study provides evidence that the airway immune cells of children are primed for virus sensing, resulting in a stronger early innate antiviral response to SARS-CoV-2 infection than in adults (Loske et al, 2021) A case series with 5 children mentioned the following long-term effects identified thus far: fatigue, dyspnea, palpitations, chest pain, headache, concentration problems, muscle weakness, dizziness and sore throat, which are more severe in girls than in boys (Ludvigsson, 2020b).…”
Section: Introductionmentioning
confidence: 99%